2021
DOI: 10.1080/02640414.2021.1999618
|View full text |Cite
|
Sign up to set email alerts
|

Is the visual impairment origin a performance factor? Analysis of international-level para swimmers and para athletes

Abstract: The aim of this study was to investigate the effect of congenital and acquired visual impairments on the 21 international performance of Para swimmers and Para track and field athletes. We collected results from 22 visually impaired Para athletes competing in Para swimming or Para athletic events at all IPC-labelled 23 competitions between 2009 and 2019. The dataset contained 20689 events results. Impairment origin was 24 collected from the International Paralympic Committee (IPC) website. We separated impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Patatas et al 7 found that athletes with congenital impairment start in Para sport approximately 8 yrs younger and win medals in international competitions 7 yrs earlier than athletes with acquired impairment, considering 345 athletes from different sports. Le Toquin et al 8 in Para Swimming athletes (11s and 12s classes) verify that the age at peak performance was achieved earlier for male and female swimmers with a congenital impairment compared with the athletes who had an acquired impairment. These studies demonstrated the importance of verifying the origin of impairment of Paralympic athletes to identify possible perspectives of performance assessments 9–11 …”
mentioning
confidence: 91%
“…Patatas et al 7 found that athletes with congenital impairment start in Para sport approximately 8 yrs younger and win medals in international competitions 7 yrs earlier than athletes with acquired impairment, considering 345 athletes from different sports. Le Toquin et al 8 in Para Swimming athletes (11s and 12s classes) verify that the age at peak performance was achieved earlier for male and female swimmers with a congenital impairment compared with the athletes who had an acquired impairment. These studies demonstrated the importance of verifying the origin of impairment of Paralympic athletes to identify possible perspectives of performance assessments 9–11 …”
mentioning
confidence: 91%
“…Krabben et al (2019) verified that 79% of visually impaired judo specialists (e.g., coaches, classifiers, physical trainers, and administrators) reported that the origin of impairment (congenital and acquired) and the age when the impairment was acquired were factors that influenced judo performance. This is supported by the studies of Patatas et al (2021) andLe Toquin et al (2022) who found that the age at acquisition of the disability could directly impact the competitive results (i.e., medals) and athletic performances.…”
Section: Discussionmentioning
confidence: 69%
“…Patatas et al (2021) analyzed 345 athletes from different sports and found that those with congenital (versus acquired) impairments started in para-sports approximately 8 years earlier and won medals in international competitions 7 years earlier than athletes with acquired impairments. Recently, Le Toquin et al (2021) investigated para-swimmers and para-track and field athletes with acquired or congenital impairments and found that the age at peak performance was achieved earlier for male and female para-swimmers with a congenital impairment, compared to the athletes with an acquired impairment who were in the specific visual class for para-swimming. These studies demonstrated the importance of considering the origin of impairment in para-athletes as a means of identifying possible factors of relevance to their performance (Krabben et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there could be a significant degree of variability among athletes with the same impairment. For instance, in subjects paralyzed with spinal cord injuries, disability depends on the level at which spinal cord is injured and varies whether the impairment is congenital or acquired [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%